Method for determining interlayer tensile strength of ceramic-based composite material based on three-point bending test

Through the three-point bending test method, combined with carbon fiber direction and bonding treatment, the interlayer tensile strength of ceramic matrix composite materials was calculated, which solved the problems of inaccurate measurement and limited scope of application in the prior art, and achieved efficient and accurate interlayer tensile strength measurement.

CN120521996APending Publication Date: 2025-08-22TIANJIN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510769003.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-10
Publication Date
2025-08-22

AI Technical Summary

Technical Problem

It is difficult to accurately measure the interlayer tensile strength of ceramic matrix composite materials in the prior art, and traditional methods have problems such as complicated testing settings, low measurement accuracy and limited application scope.

Method used

The three-point bending test method was used to calculate the interlayer tensile strength by determining the direction of carbon fiber, surface treatment and bonding of the extended sample, and combining the three-point bending fixture and stress formula.

Benefits of technology

It improves the accuracy and success rate of measurement, and is suitable for ceramic matrix composite materials with high interlayer tensile strength, solving the problems of difficult preparation of samples and conservative results in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120521996A_ABST
    Figure CN120521996A_ABST
Patent Text Reader

Abstract

The invention discloses a method for determining interlayer tensile strength of a ceramic matrix composite based on a three-point bending test. The method comprises the following steps: acquiring the geometric dimension of an original sample and determining the carbon fiber trend of the original sample; treating and bonding the bonding surface of the original sample to obtain a to-be-tested sample; the geometric dimension of the three-point bending clamp is obtained, and the placement mode of the to-be-tested sample is determined; a standard three-point bending test is carried out, and the maximum loading force in the test process is obtained; and calculating the breaking strength of the to-be-tested sample by using a three-point bending stress formula. A to-be-tested sample is prepared by bonding a plurality of original samples, a standard three-point bending test is carried out by using the to-be-tested sample, and finally, the interlayer tensile strength of the original samples is calculated by using a three-point bending beam stress expression, so that the problems that a test sample is difficult to prepare and a test result is inaccurate in an existing standard test method are solved; the efficiency and the precision of measuring the interlayer tensile strength of the ceramic matrix composite material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for measuring the interlayer tensile strength of a ceramic matrix composite material, in particular to a method for measuring the interlayer tensile strength of a ceramic matrix composite material based on a three-point bending test, and belongs to the field of aerospace technology. Background Art

[0002] Ceramic matrix composites (CMCs) are widely used in the aerospace field due to their excellent high-temperature resistance, low density, high specific strength, and oxidation resistance. Traditional metal materials (such as nickel-based superalloys) easily soften and oxidize in high-temperature environments, while CMCs can remain stable at temperatures of 1200-1600°C or even higher, greatly improving the heat resistance and fuel efficiency of aerospace vehicles. In aircraft engines, CMCs are used in turbine blades, combustion chambers, and nozzle liners, making the engines lighter and more resistant to high temperatures, improving thrust-to-weight ratios, and reducing cooling requirements. Furthermore, in spacecraft thermal protection systems (TPS), CMCs can be used in the external heat shielding of reentry capsules, supersonic vehicles, and hypersonic missiles, providing excellent ablation resistance.

[0003] Delamination is one of the primary failure modes of CMCs. The primary metric for evaluating the interlaminar mechanical properties of CMCs is the interlaminar tensile strength (ILTS). Currently, there are few methods for measuring ILTS for CMCs, and they suffer from complex test setups and low measurement accuracy. The commonly used measurement standards are ASTM D7291 and ASTM D6415. ASTM D7291 uses a direct loading method, using a plane tension test to measure ILTS. However, this method requires specimens of sufficient laminate thickness, making preparation difficult. Even if specimens are successfully prepared, internal defects can lead to overly conservative ILTS measurements. ASTM D6415 uses an indirect loading method, using a four-point bending test on a curved beam to measure ILTS. This method requires an estimate of the Young's modulus of the curved beam, which introduces significant uncertainty in the measurement results. To overcome the shortcomings of existing measurement standards, new test methods for measuring CMC ILTS are needed to meet the demand for CMC performance measurement.

[0004] Further prominent issues include: the interlaminar tensile strength of ceramic-based composites is recognized as one of the most difficult mechanical properties of this type of material to measure. The three-point bending test is a widely used and highly accepted experimental method. It is mainly used to measure the bending strength and shear strength of beams and is used in mechanical property tests of various materials. Ceramic-based composites are anisotropic materials with different mechanical properties in different directions. Therefore, the direction in which the three-point bending load is applied is different, and the measured mechanical properties are also different. In the field of composite materials, the three-point bending test generally applies pressure along the thickness direction, and the final measured value is the in-plane tensile strength and interlaminar shear strength. The interlaminar tensile strength along the thickness direction cannot be obtained. In order to obtain the interlaminar tensile strength, the three-point bending load needs to be applied perpendicular to the thickness.

[0005] In actual measurements, the interlaminar tensile strength is measured in the thickness direction of the ceramic matrix composite. However, ceramic matrix composites are thin-walled structures. Due to their preparation process and application scenarios, their thickness is relatively thin, generally less than 2 cm. This thickness is far below the lower limit of the specimen length required for tensile testing, making it impossible to achieve stable clamping. In the existing technology, the bonding block is extended in the thickness direction of the specimen, and then the tensile test is performed by clamping the block. However, the existing technology has the following problems: 1) High requirements for specimen processing: the extension block and the test piece must be strictly aligned, and the thickness of the adhesive layer must be uniform. Otherwise, the tensile stress applied to the specimen will be uneven, resulting in inaccurate (underestimated) interlaminar tensile strength test. 2) Unable to test ceramic-based composites with high interlaminar tensile strength: The adhesive layer is subjected to the same stress as the ceramic-based composite during the experiment. Therefore, the experiment must ensure that the adhesive layer does not fail before the ceramic-based composite fails. For specimens with high interlaminar tensile strength, the adhesive layer often fails before the test specimen, resulting in test failure. Because the adhesive layer strength is fixed, it can only be used to measure ceramic-based composites with low interlaminar tensile strength. Summary of the Invention

[0006] The purpose of the present invention is to provide a method for measuring the interlaminar tensile strength of ceramic matrix composite materials based on a three-point bending test in order to solve at least one of the above technical problems.

[0007] The present invention achieves the above-mentioned object through the following technical solution: a method for measuring the interlaminar tensile strength of ceramic matrix composite materials based on a three-point bending test, the method comprising the following steps: S1. Obtaining the geometric dimensions of the original sample and determining the orientation of the carbon fibers of the original sample, and determining the thickness direction by determining the orientation of the carbon fibers of the original sample; S2. Surface treatment is performed on the bonding surface of the original sample and bonding is performed to obtain a sample to be tested, and the original sample is extended in the thickness direction by bonding; S3. Obtain the geometric dimensions of the three-point bending fixture and determine the placement of the test sample; S4. Perform a standard three-point bending test to obtain the maximum load during the test; S5. Use the three-point bending stress formula to calculate the destructive strength of the sample to be tested, that is, obtain the interlaminar tensile strength of the original sample.

[0008] As a further solution of the present invention: in S1, the shape of the original sample is a rectangular parallelepiped, and the geometric dimensions of the original sample include length, width and thickness; the carbon fiber orientation distribution of the original sample is: the plane composed of the length direction and the width direction is the plane of the carbon fiber weaving arrangement, and the thickness direction is the direction of the lamination of the carbon fiber material.

[0009] As a further solution of the present invention: in S2, the bonding surface of the original sample is the plane where the carbon fibers are woven and arranged in the direction of the carbon fibers of the original sample.

[0010] As a further solution of the present invention: In S2, the surface treatment of the bonding surface of the original sample includes the following steps: removing oil, dust and moisture from the surface, polishing, pickling or using a special surface treatment agent, ensuring that the ratio of the adhesive and curing agent of the epoxy resin glue is accurate, evenly applying the glue on the bonded surface, and tightly fitting and curing the two bonded surfaces.

[0011] As a further solution of the present invention: in S2, the sample to be tested is composed of at least two original samples bonded together through their bonding surfaces, then the length and width dimensions of the sample to be tested are the average length and width dimensions of all the original samples, and the thickness dimension is obtained by directly measuring the sample to be tested after bonding.

[0012] As a further solution of the present invention: in S3, the geometric dimensions of the three-point bending fixture include the span of the lower fixture, and the span of the lower fixture is determined by the thickness of the sample to be tested.

[0013] As a further solution of the present invention: in S3, the test sample is placed symmetrically on the lower fixture of the three-point bending fixture, with the loading pressure head of the three-point bending fixture facing the middle position of the test sample.

[0014] As a further solution of the present invention: in S4, a standard three-point bending test is performed on the test sample, the magnitudes of all load forces during the test are recorded, and the maximum load force is extracted.

[0015] As a further solution of the present invention: In S5, the three-point bending stress formula in the standard three-point bending test is used to calculate the breaking strength of the sample to be tested, that is, the interlaminar tensile strength of the original sample is:

[0016] in, is the maximum load during the three-point bending test, is the span of the lower fixture, and are the length and width of the sample to be tested.

[0017] The beneficial effects of the present invention are: 1. The specimen processing requirements are low. The three-point bending test does not have strict requirements on the straightness of the beam, and its test results are not sensitive to the straightness of the beam. Therefore, the extension block and the test piece do not need to be strictly aligned, and there is no requirement for the thickness of the adhesive layer. The influence of the differences in the parts on the test results is reduced, thereby improving the success rate of the parts and the accuracy of the measurement; 2. Wide range of applications. According to the beam bending theory in "Mechanics of Materials", under three-point bending load, the tensile stress on the adhesive layer is lower than that on the test piece. That is, the adhesive layer with lower strength can be used to test composite materials with higher interlayer tensile strength. Therefore, this solution can be used to measure ceramic-based composite materials with high interlayer tensile strength. 3. The testing method described in the present invention extends multiple original specimens by bonding them together, making specimen preparation convenient, without strict alignment requirements, and achieving a high test success rate. This method solves the problems of the existing test standard ASTM D7291, which are difficult to prepare test specimens, have high alignment requirements, and have conservative test results. All parameters involved in the present invention can be uniquely determined, solving the problem of artificial assumptions regarding specific parameters in the existing test standard ASTM D6415. The present invention improves the efficiency and accuracy of measuring the interlaminar tensile strength of ceramic-based composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is the overall flow chart of the present invention; Figure 2 This is a schematic structural diagram of an original sample according to Example 2 of the present invention; Figure 3 This is a schematic structural diagram of a sample to be tested according to the second embodiment of the present invention; Figure 4 Schematic diagram of the structure of the three-point bending fixture and the sample placement method according to the second embodiment of the present invention; Figure 5 This is a load-displacement response image of the sample during the loading process recorded by the testing machine of Example 2 of the present invention. DETAILED DESCRIPTION

[0019] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0020] Example 1, as Figure 1 As shown, this embodiment provides a method for measuring the interlaminar tensile strength of a ceramic matrix composite material based on a three-point bending test, the method comprising the following steps: First: obtain the geometric dimensions of the original sample and determine the carbon fiber orientation of the original sample, and determine the thickness direction by determining the carbon fiber orientation of the original sample.

[0021] The thickness direction of the original sample is perpendicular to the carbon fiber direction. The thickness direction is easy to determine in the original sample. However, after being processed into the test sample, the dimensions are similar, so the thickness direction needs to be determined in advance.

[0022] The shape of the original sample is a rectangular parallelepiped, and the geometric dimensions of the original sample include length, width and thickness; the carbon fiber orientation distribution of the original sample is as follows: the plane formed by the length direction and the width direction is the plane of the carbon fiber weaving arrangement, and the thickness direction is the direction of the carbon fiber material lamination.

[0023] Second: The bonding surface of the original sample is surface treated and bonded to obtain a sample to be tested, and the original sample is extended in the thickness direction through bonding.

[0024] Whether it is the existing unidirectional tensile test method or the three-point bending test method newly proposed in this technical solution, it is necessary to perform bonding extension processing in the thickness direction.

[0025] The bonding surface of the original sample is the plane where the carbon fibers are woven and arranged in the direction of the carbon fibers of the original sample.

[0026] The surface treatment of the bonding surface of the original sample includes the following steps: removing oil, dust and moisture from the surface, grinding, pickling or using a special surface treatment agent, ensuring the accurate ratio of adhesive and curing agent of the epoxy resin glue, evenly applying the glue on the bonded surface, and tightly fitting the two bonded surfaces. The curing time takes 24 hours.

[0027] The test sample is composed of at least five original samples bonded together through the bonding surface. The length and width of the test sample are the average of the length and width of all the original samples, and the thickness is directly measured from the bonded test sample. The length, width and thickness of the test sample are recorded at the same time.

[0028] Third: Obtain the geometric dimensions of the three-point bending fixture and determine the placement of the test specimen.

[0029] The geometric dimensions of the three-point bending fixture include the span of the lower fixture, and the span of the lower fixture is determined by the thickness dimension of the test specimen and should be 3 / 4 to 4 / 5 of the thickness dimension.

[0030] The test sample is placed symmetrically on the lower fixture of the three-point bending fixture, with the loading head of the three-point bending fixture facing the middle of the test sample, that is, at the midline position of the test sample.

[0031] Fourth: Conduct a standard three-point bending test to obtain the maximum load during the test.

[0032] A standard three-point bending test was performed on the test specimen, the magnitude of all load forces during the test was recorded, and the maximum load force was extracted.

[0033] Fifth: Use the three-point bending stress formula to calculate the destructive strength of the sample to be tested, that is, obtain the interlaminar tensile strength of the original sample.

[0034] The three-point bending stress formula in the standard three-point bending test is used to calculate the destructive strength of the test sample, that is, the interlaminar tensile strength of the original sample is:

[0035] in, is the maximum load during the three-point bending test, is the span of the lower fixture, and are the length and width of the sample to be tested.

[0036] In actual operation, a "mechanical universal testing machine" can be used to measure the indenter pressure when the specimen is destroyed. Then, according to the above formula, the thickness direction stress when the specimen is destroyed can be calculated, which is the interlaminar tensile strength of the composite material.

[0037] Embodiment 2: This embodiment provides a method for testing the interlaminar tensile strength of a ceramic matrix composite material. The testing method is based on a three-point bending test.

[0038] The three-point bending test is a widely used and highly accepted experimental method. It is mainly used to measure the bending strength and shear strength of beams and is used in mechanical property tests of various materials.

[0039] Ceramic-matrix composites (CMCs) are anisotropic materials, with varying mechanical properties in different directions. Therefore, the measured mechanical properties vary depending on the direction in which the three-point bending load is applied. In the field of composite materials, three-point bending tests typically apply pressure along the thickness direction, resulting in in-plane tensile strength and interlaminar shear strength, but not interlaminar tensile strength along the thickness direction.

[0040] To obtain interlaminar tensile strength, the three-point bending load must be applied perpendicular to the thickness. Therefore, in this example, the specimen (original specimen) is first extended in the thickness direction before the three-point bending load is applied.

[0041] The three-point bending test is an indirect measurement method for measuring interlaminar tensile strength. The direct data obtained from the experiment is the bending load, not the tensile load. The corresponding interlaminar tensile strength must be calculated using the stress formula for beam bending. However, those skilled in the art prefer direct measurement methods, which involve stretching the specimen after bonding it. This method directly measures the interlaminar tensile strength. Direct measurement has many drawbacks (discussed in the background), which the three-point bending test can circumvent.

[0042] First choice, such as Figure 2 As shown, a batch of original rectangular samples of ceramic matrix composite materials are obtained, and the geometric dimensions of the original samples including length are measured. ,width and thickness , and then the bonding surface of the original specimen was surface treated, such as Figure 3 As shown, five samples are bonded together to obtain the test sample, and its geometric dimensions include length ,width and thickness is (can be measured directly), according to its thickness Determine the span of the lower fixture in the three-point bending test as (like Figure 3 As shown), adjust the span of the lower fixture, place the test sample symmetrically on the three-point bending lower fixture, and then perform a standard three-point bending test, as shown in Figure 4 and Figure 5 As shown, the radius is used at a constant rate of 2 mm / min R =1mm indenter is used to load, record the magnitude of all load forces during the test, and extract the maximum load force Finally, the three-point bending beam stress formula is used to calculate the destructive strength of the test sample (i.e., the interlaminar tensile strength of the original sample):

[0043] The specific values ​​of the geometric dimensions of the original specimen are shown in Table 1, the geometric dimensions of the specimen to be tested in the three-point bending test are shown in Table 2, and the span and maximum load force in the three-point bending test are shown in Table 3.

[0044]

[0045]

[0046] Working principle: Obtain the geometric dimensions of the original sample and determine the carbon fiber orientation of the original sample; perform surface treatment on the bonding surface of the original sample and bond it to obtain the sample to be tested; obtain the geometric dimensions of the three-point bending fixture and determine the placement of the sample to be tested; perform a standard three-point bending test to obtain the maximum load force during the test; use the three-point bending stress formula to calculate the destructive strength of the sample to be tested.

[0047] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be included therein. Any reference sign in a claim should not be construed as limiting the claim to which it relates.

[0048] In addition, it should be understood that although this specification is described in terms of implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

Claims

1. A method for determining the interlaminar tensile strength of ceramic matrix composite materials based on a three-point bending test, characterized in that: The method comprises the following steps: S1. Obtaining the geometric dimensions of the original sample and determining the orientation of the carbon fibers of the original sample, and determining the thickness direction by determining the orientation of the carbon fibers of the original sample; S2. Treating and bonding the bonding surface of the original sample to obtain a sample to be tested, and extending the original sample in the thickness direction by bonding; S3. Obtain the geometric dimensions of the three-point bending fixture and determine the placement of the test sample; S4. Perform a standard three-point bending test to obtain the maximum load during the test; S5. Use the three-point bending stress formula to calculate the destructive strength of the sample to be tested, that is, obtain the interlaminar tensile strength of the original sample.

2. The method according to claim 1, wherein: In S1, the shape of the original sample is a rectangular parallelepiped, and the geometric dimensions of the original sample include length, width and thickness; the carbon fiber orientation distribution of the original sample is as follows: the plane formed by the length direction and the width direction is the plane of the carbon fiber weaving arrangement, and the thickness direction is the direction of the carbon fiber material lamination.

3. The method according to claim 1, wherein: In S2, the bonding surface of the original sample is the plane where the carbon fibers are woven and arranged in the direction of the carbon fibers of the original sample.

4. The method according to claim 3, wherein: In said S2, processing the bonding surface of the original sample includes the following steps: removing oil, dust and moisture from the bonding surface of the original sample, polishing, pickling or using a surface treatment agent on the bonding surface of the original sample, applying glue on the bonding surface of the original sample, and laminating and curing the bonding surfaces of the two original samples.

5. The method according to claim 3, wherein: In S2, the sample to be tested is composed of at least two original samples bonded together through their bonding surfaces; wherein the length and width of the sample to be tested are the average of the length and width of all the original samples, and the thickness is obtained by directly measuring the sample to be tested after bonding.

6. The method according to claim 1, wherein: In S3, the geometric dimensions of the three-point bending fixture include the span of the lower fixture, and the span of the lower fixture is determined by the thickness of the sample to be tested.

7. The method according to claim 6, characterized in that: In S3, the sample to be tested is placed symmetrically on the lower fixture of the three-point bending fixture, with the loading pressure head of the three-point bending fixture facing the middle position of the sample to be tested.

8. The method according to claim 1, wherein: In S4, a standard three-point bending test is performed on the test sample, the magnitudes of all load forces during the test are recorded, and the maximum load force is extracted.

9. The method according to claim 1, wherein: In S5, the three-point bending stress formula in the standard three-point bending test is used to calculate the breaking strength of the sample to be tested, that is, the interlaminar tensile strength of the original sample is: , in, is the maximum load during the three-point bending test, is the span of the lower fixture, and are the length and width of the sample to be tested.

Citation Information

Cited By

  • Method for testing room-temperature interlayer tensile strength of laminated ceramic matrix composite material

    CN122171323A